2022
DOI: 10.1186/s12890-022-02081-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of hemodynamic types in connective tissue disease associated pulmonary hypertension: more than a subgroup of pulmonary arterial hypertension

Abstract: Objective Connective tissue disease associated pulmonary hypertension (CTD-PH) is classified as a subgroup of WHO group 1 PH, also called pulmonary arterial hypertension (PAH). However, not all CTD-PH fit hemodynamic definition of PAH. This study investigates the diversity of hemodynamic types of CTD-PH, their differences in clinical characteristics and outcomes. Method We performed a retrospective cohort study. CTD-PH patients were enrolled and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Dong et al found similar results among a group of 202 patients with different types of CTDs, of whom only approximately 10% had SSc. CTD patients with WHO Group 2 PH had worse short‐term survival but comparable 5‐year survival to those with CTD‐PAH 25 . WHO Group 3 PH due to ILD is also associated with poor outcomes.…”
Section: Is the Prognosis Of Ctd‐pah Different From Idiopathic Pah? I...mentioning
confidence: 92%
See 1 more Smart Citation
“…Dong et al found similar results among a group of 202 patients with different types of CTDs, of whom only approximately 10% had SSc. CTD patients with WHO Group 2 PH had worse short‐term survival but comparable 5‐year survival to those with CTD‐PAH 25 . WHO Group 3 PH due to ILD is also associated with poor outcomes.…”
Section: Is the Prognosis Of Ctd‐pah Different From Idiopathic Pah? I...mentioning
confidence: 92%
“…CTD patients with WHO Group 2 PH had worse short‐term survival but comparable 5‐year survival to those with CTD‐PAH. 25 WHO Group 3 PH due to ILD is also associated with poor outcomes. In fact, patients with PH associated with severe SSc‐ILD have a dismal 3‐year survival rate of 39%, which is worse than patients with SSc‐PAH without ILD.…”
Section: Is the Prognosis Of Ctd‐pah Different From Idiopathic Pah? I...mentioning
confidence: 99%
“…PH with predominant vascular disease and non-significant lung fibrosis is classified as PAH. Around 17% of patients classified as PAH-CTD demonstrate mild lung disease [37]. In a cohort of scleroderma patients with lung involvement and PH, 55% had group 3 PH, 24% had group 1 PH, and 21% had group 2 PH [38].…”
Section: Different Phenotypes Of Ph In Ildsmentioning
confidence: 98%